2014
DOI: 10.2138/am.2014.4673
|View full text |Cite
|
Sign up to set email alerts
|

Bentonite evolution at elevated pressures and temperatures: An experimental study for generic nuclear repository designs

Abstract: Geologic disposal of spent nuclear fuel in high-capacity metal canisters may reduce the repository footprint, but it may yield high-thermal loads (up to 300 °C). The focus of this experimental work is to expand our understanding of the hydrothermal stability of bentonite clay barriers interacting with metallic phases under different geochemical, mineralogical, and engineering conditions. The hydrothermal experiments were performed using flexible Au/Ti Dickson reaction cells mounted in an externally heated pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…These experiments are important in evaluating the potential effects of secondary minerals in bentonite. Such effects have been identified in bentonite hydrothermal experiments conducted by UFD (Cheshire et al, 2014), where degradation of secondary phases could yields marked effects on the altered mineral assemblage and solution chemistry.…”
Section: Benchmark 1: Salt Diffusion In Montmorillonitementioning
confidence: 97%
See 1 more Smart Citation
“…These experiments are important in evaluating the potential effects of secondary minerals in bentonite. Such effects have been identified in bentonite hydrothermal experiments conducted by UFD (Cheshire et al, 2014), where degradation of secondary phases could yields marked effects on the altered mineral assemblage and solution chemistry.…”
Section: Benchmark 1: Salt Diffusion In Montmorillonitementioning
confidence: 97%
“…• The effect of soluble or unstable phases in the buffer/backfill clay matrix: Current UFDC experimental activities on clay interactions have revealed the effects of minor phases on the high temperature degradation of barrier clay material (Cheshire et al, 2014). Benchmark 2 has provided a data set on the effect of gypsum dissolution embedded with clay.…”
Section: Potential Future Ebs-c Tasks and Outlookmentioning
confidence: 99%
“…These experiments are important in evaluating the potential effects of secondary minerals in bentonite. Such effects have been identified in bentonite hydrothermal experiments (Cheshire et al, 2014) where degradation of secondary phases could yields marked effects on the altered mineral assemblage and solution chemistry. Figure 11.…”
Section: Benchmark 2: Gypsum Dissolution In Na-and Ca-montmorillonitementioning
confidence: 98%
“…Reviews of the performance of bentonite backfill at temperatures exceeding 100 o C (e.g., Wersin et al, 2007;Pusch et al, 2010), modeling Zheng et al, 2014a), and experiment studies (e.g. Pusch et al, 2003;Caporuscio et al, 2012;Cheshire et al, 2013;Cheshire et al, 2014) of the mechanical and chemical changes at temperature up to 300 o C showed little or moderate deterioration of bentonite. While further analyses of the THMC alteration of EBS bentonite and argillite at high temperatures are warranted, these modeling (e.g.…”
Section: Layout For 12 Pwr Waste Packagementioning
confidence: 99%
“…Zheng et al, 2014a) and experimental (e.g. Cheshire et al, 2014) studies in the UFDC are suggestive that an argillite repository with EBS bentonite could sustain temperatures higher than a 100 o C. Thermal analyses with the Disposal System Evaluation Framework (DSEF) are needed to determine the drift and waste package spacing under higher thermal loads, e.g., 150 o C.…”
Section: Layout For 12 Pwr Waste Packagementioning
confidence: 99%